Permeability prediction in geotextile envelope after chemical clogging: a coupled model. Issue 6 (December 2022) - Guo, Chenyao; Zhao, Qiang; Wu, Jingwei; Li, Hang; Yang, Haoyu; Wu, Zhe
Abstract: This study develops a coupled model of chemical clogging and permeability coefficient of geotextile envelope. Based on the distribution characteristics of crystal precipitates on geotextile envelope and their influence on the permeability coefficient, a permeability coefficient model of an actual geotextile envelope that considers the overlapping effect is developed. Then, the densification effects of geosynthetic fiber hypothesis and the filter cake effect hypothesis are proposed to simulate the processes of increasing fiber diameter after crystal precipitation and the accumulation of crystal precipitates on the surface of geotextile envelope. The crystal precipitation module and permeability coefficient module are coupled, and their experimental values are used to confirm the availability of the model. Results indicate the satisfactory performance of the model. In addition, the parameter sensitivity analysis and trend prediction show that the saturation index SI and solution flow rate V are the main factors that affect the chemical clogging and permeability of geotextile envelope. When the solution conditions are not considered, the sensitivity of geotextile envelope parameter d f increased with the amount of precipitation in crystal precipitation. When the pores of the geotextile envelope are completely clogged, the permeability coefficient of the geotextile envelope will drop sharply, then decline slowly. Highlights: A coupled model for chemical clogging and permeability coefficient of geotextile envelope is developed. The densification effect of geosynthetic fiber and the filter cake effect are proposed to generalize chemical clogging. The sensitivity of geotextile envelope parameter d f increased with the amount of precipitation.